2022
DOI: 10.3390/jcm11123543
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intravenous Lidocaine in Perioperative Medicine: Anaesthetic, Analgesic and Immune-Modulatory Aspects

Abstract: This narrative review provides an update on the applied pharmacology of lidocaine, its clinical scope in anaesthesia, novel concepts of analgesic and immune-modulatory effects as well as the current controversy around its use in perioperative opioid-sparing multi-modal strategies. Potential benefits of intravenous lidocaine in the context of cancer, inflammation and chronic pain are discussed against concerns of safety, toxicity and medico-legal constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 84 publications
2
23
0
Order By: Relevance
“…Lidocaine, a local anesthetic drug, blocks the sodium-potassium channel [ 11 ], thus alleviating postoperative pain [ 12 16 ] through the following mechanisms: analgesic, anti-hyperalgesic, and anti-nociceptive [ 17 ]. Furthermore, lidocaine serves as a N-methyl-D-aspartate (NMDA) receptor antagonist [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine, a local anesthetic drug, blocks the sodium-potassium channel [ 11 ], thus alleviating postoperative pain [ 12 16 ] through the following mechanisms: analgesic, anti-hyperalgesic, and anti-nociceptive [ 17 ]. Furthermore, lidocaine serves as a N-methyl-D-aspartate (NMDA) receptor antagonist [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lidocaine serves as a N-methyl-D-aspartate (NMDA) receptor antagonist [ 18 ]. Perioperatively administered lidocaine also has anti-inflammatory activity [ 17 , 19 24 ] and facilitates the return of bowel function after abdominal surgery [ 9 , 16 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1950s, as research on the molecular mechanism of lidocaine deepened, it was found that lidocaine can not only block sodium ion channels ( Gawali et al, 2015 ) but also has critical effects on hyperpolarization-activated cyclic nucleotide-gated (HCN) channels. A certain inhibitory effect, which changes the conduction of action potentials, had analgesic properties ( Zhou et al, 2015 ; De Cassai et al, 2021 ; Foo et al, 2021 ; Lee and Schraag, 2022 ) and played an important role in pain management ( Dunn and Durieux, 2017 ; Soto et al, 2018 ). However, due to its poor water solubility and short half-life, the drug effects only last for 2 h, and thus it often requires the repeated administration to obtain satisfactory results to satisfy clinical application ( Liu and Lv, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine is on the essential drug list of World Health Organization for both its multiple anesthetic and anti‐arrhythmic indications and is considered efficacious, versatile, readily available, safe, and cost‐effective 5,6 . Through use‐dependent inhibition of individual voltage‐gated sodium channels (Na v ), and thus nerve fiber impulse generation, subsequent signaling transmission to and within the central nervous system is impeded 7,8 . Lidocaine can interact with multiple targets, but its primary clinical site is the local anesthetic binding site on the 9 mammalian Na v isoforms, with subtypes Na v 1.3, Na v 1.7, Na v 1.8, and Na v 1.9 key players in nociceptive signaling.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Through use-dependent inhibition of individual voltage-gated sodium channels (Na v ), and thus nerve fiber impulse generation, subsequent signaling transmission to and within the central nervous system is impeded. 7,8 Lidocaine can interact with multiple targets, but its primary clinical site is the local anesthetic binding site on the 9 mammalian Na v isoforms, with subtypes Na v 1.3, Na v 1.7, Na v 1.8, and Na v 1.9 key players in nociceptive signaling. Na v 1.7 channels are of particular importance as they are expressed in peripheral terminals of sensory neurons, within the dorsal route ganglion and on the sensory afferents in the superficial laminae of the spinal cord.…”
mentioning
confidence: 99%